2018
DOI: 10.1016/j.ijwd.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and sexual health in patients with hidradenitis suppurativa

Abstract: BackgroundHidradenitis suppurativa (HS) is a chronic, recurrent, debilitating follicular disease. The effect of HS on physical and psychological aspects of sexual function is not well understood.ObjectiveThe objective of this study is to investigate the contribution of sexual dysfunction to the quality of life (QoL) of patients with HS and to investigate the extent to which sexual health predicts the QoL in these patients.MethodsThis is an observational cross-sectional study of 50 patients with HS and 50 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 23 publications
4
67
1
1
Order By: Relevance
“…There was no significant difference between female patients with HS and controls regarding sexual functioning. The presence or absence of genital lesions in both male and female HS patients did not correlate with changes in DLQI scores or any sexual function measures …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference between female patients with HS and controls regarding sexual functioning. The presence or absence of genital lesions in both male and female HS patients did not correlate with changes in DLQI scores or any sexual function measures …”
Section: Resultsmentioning
confidence: 99%
“…The presence or absence of genital lesions in both male and female HS patients did not correlate with changes in DLQI scores or any sexual function measures. 74…”
Section: Studies On Qol and Sexual Problems In Hs Patientsmentioning
confidence: 99%
“…Alavi and colleagues performed an observational cross‐sectional study of 50 HS patients compared with 50 healthy volunteers. HS cases were derived from those who presented at the Women's College Hospital or Richmond Hill Dermatology Clinic between 2015 and 2016 in Canada, with diagnosis confirmed by a dermatologist.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17][18] Two studies 14,18 were based on institutional based data, whereas three studies [15][16][17] used population based registry data. Two studies 14,18 required HS diagnosis confirmed by a dermatologist, whilst the others used disease classification codes for databases. Three studies 14,16,18 reported matching between case and control groups.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…HS is regarded as autoinflammatory in its origin on the basis of the centrality of innate immunity dysfunction in its pathogenesis, with however a contributory role of adaptive immunity changes . Clinically, it is characterized by painful nodules, abscesses, and sinus tracts and has a tremendous impact on quality of life . Pain is one of the most important and debilitating features of this disease, and it is usually much higher than in other chronic‐relapsing inflammatory skin diseases such as psoriasis and atopic dermatitis .…”
Section: Introductionmentioning
confidence: 99%